Nano-fluorophores prepared by polymerization-induced self-assembly and its application in cell imaging. (June 2021) - Wang, Junhao; Zhu, Yichuan; Zhou, Shixin; Wu, Weichun; Tong, Qin; Hu, Jianghong; Min, Shenxi; Hou, Guangliang; Dong, Bin; Song, Bo
Abstract: In this work, we report a nano-fluorophore prepared by polymerization-induced self-assembly (PISA) method based on reversible addition-fragmentation chain transfer polymerization. The macromolecular chain transfer agent was polyethylene glycol-based trithiocarbonate, and the monomer was a chalcone derivative terminated with ethylene group. The reaction/assembly was conducted in dioxane, where nanoparticles with extremely uniform size (~200 nm) was formed. The nanoparticles were transferred into aqueous solution, and shrank to ~100 nm with excellent dispersion. The nanoparticles showed fluorescence emission at around 570 nm, and after being transferred to aqueous solution, the emission intensity was significantly enhanced. Being covered with hydrophilic polyethylene glycol, the nano-fluorophores possess excellent biocompatibility, and was successfully applied to label HeLa cells for fluorescent imaging. This study presents a novel avenue for including fluorescent dyes into polymeric nanoparticles with narrow size-distribution, tailorable solubility and biocompatibility. Graphical abstract: Image 1 Highlights: Nanoparticles including chalcone derivatives were prepared using polymerization-induced self-assembly method. The nanoparticles are well dispersed in water with diameter of ~ 100 nm and narrow size-distribution. The excellent fluorescent emission and good biocompatibility of the nanoparticles allow for high-contrast cell-imaging.